A Systematic Literature Review of Integrated Learning Models for Skills Development in Industry-Academia Partnerships: Preparing Workforce for Industry 4.0 - Ricky Cahyasari Putra; Mokhamad Syaom Barliana; Mumu Komaro; Aam Hamdani (Universitas Sultan Ageng Tirtayasa, 2025)
The Industry 4.0 revolution has created significant skills gaps between formal education outcomes and evolving industry requirements, necessitating innovative industry-academia partnerships. This systematic literature review analyzes integrated learning models addressing these challenges. Following PRISMA guidelines, we searched Scopus, Web of Science, ERIC, and Science Direct databases (2021-2025) using keywords combinations of